Evaluation of an immunocapture-agglutination test (Brucellacapt) for serodiagnosis of human brucellosis, Ilam, Iran - Maleki, Abbas; Ghafourian, Nasim; Ghofourian, Sobhan; Pakzad, Iraj; Sadeghifard, Nourkhoda; Khosravi, Afra; Asadolahi, Khayrolah; Sekawi, Zamberi; Mohebi, Reza; Hemation, Ali; Hosseinzadeh, Moreteza (IDOSI Publications, 2011)
Brucellosis is common health problem in some Middle Eastern, Mediterranean countries and Iran. The present investigation was carried out to investigate the prevalence of brucella antibodies through Rose bengal test (RBT), Wright and Coombs and comparison with Brucella Capt Test. A total of 754 different suspected to brucellosis were tested during the period from March 2008 to February 2009. They assayed by Brucellacapt, Coombs tests and SAT. Our results had shown that of 754 serum samples, 125 samples were positive by Rosbangal test. Thus, frequency of brucellosis by Rosbangal test was 16.5%. The results in 1/40 and 1/80 were equal for Brucellacapt and Coombs test and different for SAT. The other titers results were different for all testes which used in our study. The results from the present study showed a high sensitivity and specificity of Brucellacapt for the diagnosis of human brucellosis.